Linking benefits to maturity models - Gomes, J.; Romão, M.; Caldeira, M. (Proceedings of the 15th Conference of the International Academy of Management and Business (IAMB), 2013)
Many organizations today need to deliver more complex products and services in a better, faster, and cheaper way. The business problems that some companies address require enterprise-wide solutions that call for an integrated approach and an effective management of organizational resources to achieve business objectives with an acceptable level of risk. A maturity model is a process improvement approach that provides organizations with the essential elements of effective change. It can be used to guide process improvement across a project, a division, or an entire organization. Maturity models help integrate traditionally separate organizational functions, set process improvement goals and priorities, provide guidance for quality processes, and provide benchmark for appraising current processes outcomes. The benefits management approach emerges as a complement to traditional management practices and proposes a continuous mapping of benefits, implementing and monitoring intermediate results. Benefits management reinforces the distinction between project results and business benefits. Based on a case study the authors show how a set of business objectives can be obtained from identifying, structuring and monitoring business benefits, supported by information technology enablers and organizational transformations, and as a result of a certain maturity level. The authors also state that the main focus of an investment success lies not only in technology implementation, but mainly in changes in organizational performance and business efficiency by means of improved processes and modifications in the way the work is done. We emphasize that the integration between a Maturity Model and a Benefits Management approach can increase the effectiveness of projects, programs or portfolios outcomes. Besides, this linkage can also improve decision-makers confidence that the investments done match the desired maturity stages and will then, with more probability, collect more value for businesses.